The crystal structure of dichlorido-[(E)-N′,N″-bis((2E,3E)-3-(hydroxyimino)butan-2-ylidene)-2-((E)-3-(hydroxyimino)butan-2-ylidene)hydrazine-1-carbohydrazonhydrazide-κ 4 N 4]cobalt(II), C13H22N9O3Cl2Co - Zhai Zhi-Wei; Yang Shuang-Hua (Zeitschrift für Kristallographie - New Crystal Structures)
C13H22N9O3Cl2Co, monoclinic, P21/n (no. 14), a = 7.7939(4) Å, b = 23.1095(11) Å, c = 11.7358(7) Å, β = 108.179(6)°, V = 2008.3 (2) Å3, Z = 4, R gt(F) = 0.0485, wR ref(F 2) = 0.1002, T = 293(2) K.